Sick building syndrome among healthcare workers and healthcare associates at observed general hospital in Slovenia - Kalender-Smajlović, Sedina; Dovjak, Mateja; Kukec, Andreja (Central European Journal of Public Health, 2021)
OBJECTIVE: The aim of this study was to assess the possible associations between self-perceived sick building syndrome (SBS) symptoms among healthcare workers and healthcare associates and self-perceived parameters of indoor work environment quality. METHODS: The cross-sectional study was conducted from February to April 2019. Validated standardized evaluation tools (MM 040 NA Hospital 2007 and MM 040 NA Office 2007) were used for estimating the prevalence of SBS among observed populations. Chi-square and Mann-Whitney U tests for assessing possible associations in SBS symptoms between healthcare workers and associates were used. RESULTS: The response rate was 69.8%. The results showed a lower prevalence of six or more SBS symptoms in healthcare associates (6.4%) compared to healthcare workers (12.0%). Healthcare workers perceived the most frequent risk factors for SBS to be poor air quality, an inappropriate level of relative humidity, and inappropriate room temperature, while the least frequently self-perceived risk factors were inappropriate lighting and noise levels. CONCLUSIONS: This study represents a platform for further analyses - the identification of health risk factors with environmental monitoring.
Keywords: Air Pollution, Indoor; Sick Building Syndrome; Hospitals, General; Humans; zdravotnický personál; Slovinsko; Cross-Sectional Studies; nemocnice všeobecné; průřezové studie; syndrom nezdravých budov; znečištění vzduchu ve vnitřním prostředí; poskytování zdravotní péče; Delivery of Health Care; Health Personnel; lidé; Slovenia